2017
DOI: 10.1097/mat.0000000000000616
|View full text |Cite
|
Sign up to set email alerts
|

A Membrane Lung Design Based on Circular Blood Flow Paths

Abstract: Current hollow fiber membrane lungs feature a predominantly straight blood path length across the fiber bundle, resulting in limited oxygen transfer efficiency due to the diffusion boundary layer effect. Using computational fluid dynamics and optical flow visualization methods, a hollow fiber membrane lung was designed comprising unique concentric circular blood flow paths connected by gates. The prototype lung, comprising a fiber surface area of 0.28 m2, has a rated flow of 2 L/min and the oxygenation efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Computational flow dynamics and in vivo testing of this low-resistance device demonstrated that the mixing of blood as it traversed the gated compartments augmented O 2 transfer and sufficiently removed CO 2 at a rated flow of 2 L/min. 46 The compliant thoracic artificial lung consists of a flexible chamber containing a mat of hollow-fiber bundles through which blood is routed by means of inlet and outlet conduits, while fresh gas flows adjacently. 47 Initial animal experiments with this device showed that the load on the right ventricle could be reduced with the device positioned between the pulmonary artery and left atrium, and flows Ͼ 7 L/min could be achieved.…”
Section: Wearable Ecmomentioning
confidence: 99%
“…Computational flow dynamics and in vivo testing of this low-resistance device demonstrated that the mixing of blood as it traversed the gated compartments augmented O 2 transfer and sufficiently removed CO 2 at a rated flow of 2 L/min. 46 The compliant thoracic artificial lung consists of a flexible chamber containing a mat of hollow-fiber bundles through which blood is routed by means of inlet and outlet conduits, while fresh gas flows adjacently. 47 Initial animal experiments with this device showed that the load on the right ventricle could be reduced with the device positioned between the pulmonary artery and left atrium, and flows Ͼ 7 L/min could be achieved.…”
Section: Wearable Ecmomentioning
confidence: 99%
“…Data from our previous work were used to provide the necessary resistance data to simulate the fiber bundle as an isotropic porous media. 26 The experimental resistance data for the original fiber mat (17 fibers/cm) were scaled down linearly by multiplying by a factor κ κ LR , where κ LR is the predicted permeability of the low-resistance fiber mat (six fibers/cm) into equation 1. This provided the resistance data for the low-resistance fiber mat to be input into the porous media model for the CFD simulations.…”
Section: Computational Fluid Dynamicsmentioning
confidence: 99%
“…The required gas exchange SA for the current device was estimated by scaling our previous design, which had a SA = 0.28 m 2 and a rated flow of 2 L/min, but a pressure drop of approximately 100 mm Hg. 26 Scaling down SA linearly (assuming equivalent gas exchange efficiency in the previous and new designs) gave a basis SA of 0.1 m 2 for the new design because this SA is expected to provide the necessary gas exchange to satisfy the rated flow requirement. Blood flow was simulated using the Solidworks Flow Simulation add-in (Dassault Systémes), and velocity and pressure profiles were generated (Figure 2).…”
Section: Computational Fluid Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations